Material flow analysis of carbon and material flow cost analysis in a selected oil palm plantation and palm oil mill / Muhamad Hariz Mohd Zain - Muhamad Hariz , Mohd Zain (2015)
To improve the imbalance global carbon cycle that cause global warming Malaysian Government is committed to reduce its carbon dioxide emission intensity to 40% GDP per capita by 2020 as compared to 2005 level. This research aims to determine the carbon stocks, carbon cycles and carbon metabolism in selected oil palm industry and plantation in the year 2012. Material Flow Analysis (MFA) is used to determine the inputs, losses and waste of palm oil production line of the year 2012 and finally to suggest mitigation measures for impacts of carbon in the environment. This research involves data collection, site visits and the application of MFA and (Material Flow Cost Accounting) MFCA to calculate carbon stocks and losses in the system. Carbon stocks at the plantation, upstream mill, anaerobic digester and compost field for 2012 were 9,122,241.92 MT C/year, 1,364,899.82 MT C/year, -170,294.17 MT C/year and -259,402.22 MT C/year respectively. Total material losses and energy losses in the production line in 2012 were RM 4,061,991.39 and RM 18,241,516.80 respectively. To mitigate carbon losses within the palm oil metabolism system, recycling of empty fruit bunches (EFB) and palm oil mill effluent (POME) recycling were the best mitigation measures.